2020
DOI: 10.1039/d0nj01590c
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite encapsulated Ni(ii) Schiff-base complexes: improved catalysis and site isolation

Abstract: Two series of zeolite encapsulated Ni(II) Schiff-base complexes e.g., {Ni(II) sal-1,2-phen and Ni(II) sal-1,3-phen series} have been synthesized in neat and encapsulated states and characterized by different characterization techniques...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The presence of Ni 2+ was confirmed by the Ni2p3/2 and Ni2p1/2 peaks appearing at binding energies of 855.7 and 873.5 eV, respectively, for Catalyst 1 (Figure 5 (b)), along with two satellite broad peaks at the binding energies of 861.6 and 879.7 eV, respectively. This indicates that the environment around the metal center is disturbed [10] . The N1s peaks were observed at 399.4 eV for Catalyst 1 was ascribed to imine or amide groups (C=N).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of Ni 2+ was confirmed by the Ni2p3/2 and Ni2p1/2 peaks appearing at binding energies of 855.7 and 873.5 eV, respectively, for Catalyst 1 (Figure 5 (b)), along with two satellite broad peaks at the binding energies of 861.6 and 879.7 eV, respectively. This indicates that the environment around the metal center is disturbed [10] . The N1s peaks were observed at 399.4 eV for Catalyst 1 was ascribed to imine or amide groups (C=N).…”
Section: Resultsmentioning
confidence: 97%
“…This indicates that the environment around the metal center is disturbed. [10] The N1s peaks were observed at 399.4 eV for Catalyst 1 was ascribed to imine or amide groups (C=N). In the case of Catalyst 1, the lower steric hindrance of the bidentate ligand may afford the proximity between the Ni metal centers, resulting in the formation of a dimeric species.…”
Section: Chemistryselectmentioning
confidence: 97%
“…It was found that there was a certain degree of metal coordination structure in the coating. The binding energies of the 2p3/2 and 2p1/2 Ni (II) peaks in Nickel(II) acetate tetrahydrate were 856.2 and 873.9 eV, respectively [ 35 , 36 ]. After coordination with the polymer, the binding energy decreased to 854.7 and 872.1 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The 48 . Compared with the isolated nickel metal, which exhibited a Ni 0 (2p 3/2 ) binding energy (BE) of 853 eV, the ITQ-2supported nickel showed higher BEs (∼856 eV) for Ni 0 (2p 3/2 ) due to the electronic influence of the zeolite support 49 . It has been reported that interactions of metal clusters with oxygens in the zeolite framework gave rise to positive charges on the metal surface and higher BEs for the metal nanoclusters 50,51 .…”
Section: Physicochemical Properties Of the Ni/zeolite Materialsmentioning
confidence: 99%